Ministry of Civil Aviation Decree No. 666 of the Year 2021 Issued on 20/9/2021 = وزارة الطيران المدنى قرار رقم 666 لسنة 2021 الصادر فى 20/9/2021 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic